High Sn-2 Docosahexaenoic Acid Lipids for Brain Benefits, and Their Enzymatic Syntheses: A Review. (April 2020) - Jin, Jun; Jin, Qingzhe; Wang, Xingguo; Akoh, Casimir C.
Abstract: The normal development and maintenance of central neural functions are highly correlated with the amount of docosahexaenoic acid (DHA; ω-3 fatty acid) accumulated in the brain. DHA incorporated at the sn -2 position of lipids is well absorbed by intestinal mucosa and utilized efficiently in vivo . However, modern consumers have a reduced direct intake of DHA and increased intake of saturated fats or ω-6 fatty acid oils, resulting in behavioral and neurophysiological deficits. To provide an understanding of the integrated beneficial effects of DHA on the human brain, this review introduces the positional difference ( sn -2 and sn -1, 3 positions) of DHA on a glycerol skeleton in natural fats and oils, and further discusses the possible functional mechanism regarding DHA supplementation and the gut–brain axis. The multiple bidirectional routes in this axis offer a novel insight into the interaction between DHA supplementation, the gut microbiota, and brain health. To achieve high sn -2 DHA in diets, it is suggested that sn -2 DHA lipids be enzymatically produced in more efficient and economical ways by improving the specific activities of lipases and optimizing the purification procedures. These types of diets will benefit individuals with strong needs for sn -2 ω-3 lipids such as infants, children, and pregnant and lactating women.